Exploring the experiences of adolescent migrants in South Africa through applied drama and theatre: A case study of Supreme Educational College, (Johannesburg) - Zvakawapano, Wendy Paidamoyo (My University, 2014)
This study explored adolescent migrants’ experiences in South Africa through the use of applied drama and theatre strategies. The sample size included a group of 20, Grade 10 participants from Supreme Educational College who are between the ages of 15 and 16 years. The group of participants was made up of South African, Zimbabwean and Zambian nationals. The research used the metaphor of the story of the seal girl, which is an adaptation of the Irish folktale, The Seal Wife. Image Theatre was used together with the story as a way of gaining entry into the personal experiences of adolescent migrants. Through this form of enhanced image theatre, the intention was to create safe distance which was critical in the exploration and reflection of the adolescent migrants’ experiences of the South African diaspora. Augusto Boal’s theatre of the oppressed was used as the theoretical lens guiding this study. Reference was also made to Postcolonial theory which helped me to understand how the adolescent migrants construct their identities, as well as how they can understand them as fluid and not static. The study was carried out through performance ethnography as the methodological approach to the study. Performance ethnography was critical to this study because it provided a body-centred approach to investigation which privileged the body as an archive for participants’ deeply personal experiences.